2007
DOI: 10.4321/s0365-66912007001000006
|View full text |Cite
|
Sign up to set email alerts
|

Estrabismo y cataratas congénitas

Abstract: RESUMENObjetivo: Estudiar la prevalencia, características, indicaciones y resultados del tratamiento del estrabismo asociado a catarata congénita. Método: Estudio retrospectivo de 21 casos de 29 con cataratas congénitas que presentaron la asociación estrabismo y catarata (unilateral en 11 y bilateral en 10), de los que en 20 se realizó su extracción, introduciendo lente intraocular en 15. Se indicó tratamiento del estrabismo con toxina o cirugía si la desviación era estable después de completar la rehabilitaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Weisber et al, Hiles and Sheridan, and Merino reported success rates between 75 and 83.3% in older children. 9,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Weisber et al, Hiles and Sheridan, and Merino reported success rates between 75 and 83.3% in older children. 9,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Cataracthas profound consequenceson the quality of life and with a greater impacton children compared to adults. Untreated cataract predisposes children to ocular comorbidities such as amblyopia [9], strabismus [32], and nystagmus [33]. The associated vision loss could compromiseacademic performance [16,17], social relations [34], career aspiration [35] and mental health [18].…”
Section: Discussionmentioning
confidence: 99%